Efektivitas Waktu Pengeringan Udara Alamiah terhadap Kualitas Lempuyang (Zingiber zerumbet) Menggunakan Tipe Pengeringan Batch Dryer - Hyldegardis Naisali; Martha Kore; Maria Angelina Tuas (Fakultas Pertanian, Universitas Timor, 2022)
This research was conducted from August to September 2021 at the Faculty of Agriculture, University of Timor and quality analysis at the Laboratory of Mathematics and Natural Sciences, Widya Mandira Catholic University, Kupang. The purpose of this study was to determine the effectiveness of natural air drying time on the quality of lempuyang (Zingiber Zerumbet) which was dried using a batch dryer, and to determine the content of flavonoid compounds and tannins in lempuyang using natural air drying. In this study, the total weight of lempuyang tuber slices was 60 kg which was obtained from Noepesu Village, West Miomaffo District, using a drying time of 5 hours, 10 hours and 15 hours. This study is an experimental study designed using a single factor Completely Randomized Design with drying time (A) treatment consisting of 3 levels, namely drying time of 5 hours (A1), 10 hours (A2) and 15 hours (A3) and repeated 2 times. so there are 6 treatment units. Drying was carried out with a thickness of 3 mm. The results showed that the drying time of lempuyang (Zingiber zerumbet) affected the levels of flavonoids and tannins contained in it. The optimum drying time is found at 5 hours of drying with a flavonoid content of 507.96 mg/g and a tannin content of 99.29 mg/g with a final moisture content of 9.19% ww. The best drying time is at 5 hours of drying where the highest flavonoid content is 507.96 mg/g.